An Unusual Case of Xanthoma of Bilateral Achilles Tendon with Gouty Infiltration: A Rare Case Report - Khatoon, Heena M.; Srirambhatla, Annapurna; Sharma, Abhimanyu; Sankepally, Poojitha; Arora, Abhishek J. (Indian Journal of Radiology and Imaging, 2023)
Achilles tendon xanthoma is a benign and rare disease with a high incidence in patients having familial hypercholesterolemia. Patients present with or without pain and thickened tendons. Gout is seen in patients with hyperuricemia. Coexistence of xanthoma and gout is extremely rare. We searched the PubMed literature with ‘Xanthoma’ and ‘Gout’ as keywords and could find only one case report. Imaging modalities such as radiography and ultrasonography, play a vital role in diagnosing this condition early, hence helping the patient to commence the use of potentially lifesaving lipid-lowering therapeutic agents. Magnetic resonance imaging is helpful in delineating the morphological changes, exact measurements, and eventually in treatment planning. It helps to rule out early involvement of other tendons by the same pathology. We present a case of a 25-year-old male patient who presented to our institute with bilateral large symmetrical swelling in the posterior aspects of ankles for 4 years, with normal serum and blood parameters. Bilaterality, enormous size and normal blood and serum parameters make this case unique.
Keywords: Achilles tendon; xanthoma; gout; ultrasonography; radiography; MRI